Dopant‐Free Partial Rear Contacts Enabling 23% Silicon Solar Cells. Issue 9 (18th January 2019) - Bullock, James; Wan, Yimao; Hettick, Mark; Zhaoran, Xu; Phang, Sieu Pheng; Yan, Di; Wang, Hanchen; Ji, Wenbo; Samundsett, Chris; Hameiri, Ziv; Macdonald, Daniel; Cuevas, Andres; et al.
Abstract: Over the past five years, there has been a significant increase in both the intensity of research and the performance of crystalline silicon devices which utilize metal compounds to form carrier‐selective heterocontacts. Such heterocontacts are less fundamentally limited and have the potential for lower costs compared to the current industry dominating heavily doped, directly metalized contacts. A low temperature (≤230 °C), TiO x /LiF x /Al electron heterocontact is presented here, which achieves mΩcm 2 scale contact resistivities ρc on lowly doped n‐type substrates. As an extreme demonstration of the potential of this heterocontact, it is trialed in a newly developed, high efficiency n‐type solar cell architecture as a partial rear contact (PRC). Despite only contacting ≈1% of the rear surface area, an efficiency of greater than 23% is achieved, setting a new benchmark for n‐type solar cells featuring undoped PRCs and confirming the unusually low ρc of the TiO x /LiF x /Al contact. Finally, in contrast to previous versions of the n‐type undoped PRC cell, the performance of this cell is maintained after annealing at 350–400 °C, suggesting its compatibility with conventional surface passivation activation and sintering steps. Abstract : An electron‐selective TiO x based heterocontact is developed and trialed as a dopant‐free partial rear contact in high efficiency silicon solar cells. This cell not only reaches an efficiency of above 23% but also maintains its performance after a short anneal at 400 °C—setting new benchmarks of performance and thermal stability for this cell architecture.